Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s13202-021-01136-y
|View full text |Cite
|
Sign up to set email alerts
|

Velocity anisotropy and trend in Niger Delta, Nigeria

Abstract: In geophysical data interpretation, matching the vertical velocity direction from seismic data with borehole-derived velocities is a challenging task because seismic-derived velocities are faster than borehole recorded velocities. This geophysical phenomenon is caused by velocity anisotropy. In this study, we used an empirical approach to estimate the degree of velocity anisotropy in the study area. The results showed that the delta anisotropy in sandstone beds varies from − 2.5% to 7.2% while most of them con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The next years are rich in new researches that expands the understanding of the origin and impacts of anisotropy, especially when related to shales. Dewhurst and Siggins (2006), Singh and Sircar (2014), Okorie et al (2016) and Aniwetalu et al (2021) present important considerations about the magnitudes of anisotropy observed in shales, indicating that it is a lithology with characteristics conducive to the phenomenon, especially regarding the alignment of clay minerals.…”
Section: Introductionmentioning
confidence: 99%
“…The next years are rich in new researches that expands the understanding of the origin and impacts of anisotropy, especially when related to shales. Dewhurst and Siggins (2006), Singh and Sircar (2014), Okorie et al (2016) and Aniwetalu et al (2021) present important considerations about the magnitudes of anisotropy observed in shales, indicating that it is a lithology with characteristics conducive to the phenomenon, especially regarding the alignment of clay minerals.…”
Section: Introductionmentioning
confidence: 99%